Point Systems and International Student Flows - Li, Jing (International Higher Education, 2014)
This article is aimed to examining the impact of using point systems to select immigrant on the international student flows, by comparing the international student stock in a certain country before and after the policy change. The research indicates that using point systems in migration policy does increase the international student stock in the receiving countries.